2019
DOI: 10.1093/nar/gkz732
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of La/SSB-dependent viral gene expression by pre-tRNA 3′ trailer-derived tRNA fragments

Abstract: tRNA-derived RNA fragments (tRFs) have emerged as a new class of functional RNAs implicated in cancer, metabolic and neurological disorders, and viral infection. Yet our understanding of their biogenesis and functions remains limited. In the present study, through analysis of small RNA profile we have identified a distinct set of tRFs derived from pre-tRNA 3′ trailers in the hepatocellular carcinoma cell line Huh7. Among those tRFs, tRF_U3_1, which is a 19-nucleotide-long chr10.tRNA2-Ser(TGA)-derived trailer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 53 publications
0
48
2
1
Order By: Relevance
“…Additionally, Kay and colleagues showed that the RNase Z/ELAC2 produces 3′ trailer tRFs in human cell lines ( 31 ). With regard to localization, the presence of ELAC2 in the cytoplasm and the production of 3′ trailer tRFs in the cytoplasm is supported by the work of Dutta and colleagues ( 2 ) and Oh and colleagues ( 32 ). However, it is not clear how pre-tRNA molecules are exported to the cytoplasm.…”
Section: To Stress or Not To Stress About It?mentioning
confidence: 82%
“…Additionally, Kay and colleagues showed that the RNase Z/ELAC2 produces 3′ trailer tRFs in human cell lines ( 31 ). With regard to localization, the presence of ELAC2 in the cytoplasm and the production of 3′ trailer tRFs in the cytoplasm is supported by the work of Dutta and colleagues ( 2 ) and Oh and colleagues ( 32 ). However, it is not clear how pre-tRNA molecules are exported to the cytoplasm.…”
Section: To Stress or Not To Stress About It?mentioning
confidence: 82%
“…Another mechanism for gene silencing by tRFs is through competitive binding of target proteins with mRNAs. For example, unlike the above mechanism of tRF in viral infections, a chr10.tRNA2-Ser(TGA)-derived 1-tRF, tRF_U3_1, can bind directly to La/SSB protein and inhibit La/SSB-dependent viral gene expression [46]. This means that tRFs may have involvement in multiple different mechanisms within the same disease.…”
Section: Rna Silencingmentioning
confidence: 99%
“…In hepatocellular carcinomas (HCC), tRF_U3_1 is more abundant in the HCC cell line Huh7 and cancerous liver tissues compared to primary hepatocytes and normal liver tissues, which can inhibit viral gene expression and its precursors [46]. Whether the inhibition of viral gene expression by tRF_U3_1 has an impact on HCC still requires verification.…”
Section: Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…42 It has been reported that, originating from the pre-tRNA tail region, tRF regulates viral gene expression by isolating La/SSB in the cytoplasm. 43 Some researchers conducted Ago-immunoprecipitation (Ago-IP) tRF analysis and, using bioinformatics methods, found that tRF-5 mainly exists in multiple Ago-IPs in addition to Ago2-IP, while Ago2-IP has the strongest interaction with tRF-3. 44 Since only Ago2 in mammals contains a slicer domain, Daugaard et al speculated that the interaction of Ago2-tRF-3 might suppress the antisense reporter genes by directly cutting the target transcripts.…”
Section: Introductionmentioning
confidence: 99%